Swedish political party programs and election manifestos - Swedish National Data Service, University of Gothenburg (University of Gothenburg, 2022)
Swedish party programs and election manifestos from 1897 until today.

All documents are also open available at page: https://snd.gu.se/vivill, where it is possible to search in the documents.

Swedish party programs and election manifestos builds on the "Vi vill …! Hundra år av partipolitiska viljeyttringar" ("We want…! A hundred years of political party declarations") project, which the predecessor of SND, SSD, conducted in 2000–2002. The purpose of this project was to collect the programs and manifestos that the political parties had produced during the 20th century. In these texts, you can trace the development of the political parties in terms of their language, politics, and ideology. The material also provides an overview of which questions have been essential for the development of Sweden.

The selection of election manifestos builds on work done by Sven-Olov Håkansson in "Svenska valprogram 1902–1952" (”Swedish election programs 1902–1952”), and materials collected and used in the research project "Partiernas opinionspåverkan" (“Political party influence on public opinions”), POP, by Peter Esaiasson and Nicklas Håkansson. At first, only political parties in the Swedish Parliament (Sveriges riksdag) were represented in the material. Later additions have given a broader selection of parties as well as party documents related to the European Parliament elections.

In the case of party programs, we have searched in research libraries and people’s movement libraries, as well as in the archives of the political parties. As there is varying degrees of knowledge about which programs have been produced, we are aware that we have probably been unable to find an unknown number of documents that could otherwise have been included in the collection.

This project was made possible thanks to John-Erik Ågotnes at NSD (Norsk Samfunnsvitenskapelig Datatjenste, now SIKT), the Norwegian counterpart to SSD, which in 1997 published a CD with Norwegian party programmes. Ågotnes allowed SSD free use of the software he had developed for his project.

The "Vi vill …" project was awarded financial support from the Riksbankens Jubileumsfond grant for support to research infrastructures.

The dataset consists of:
- The zip file "Svenska partiprogram och valmanifest" that consists of the folder "Partidokument" which contains all political party documents in .pdf and .txt format sorted in separate folders for each party
- The documentation files "Partidokument" where the .xlsx and .csv documents listing all party documents, their type, source and titles as well as a "readme" .txt file.

Access to data: https://snd.gu.se/en/vivill

De svenska partiernas partiprogram och valmanifest från 1897 fram till idag.

Dokumenten finns öppet tillgängliga via denna länk: https://snd.gu.se/vivill. Här går också att söka i dokumenten.

Svenska partiprogram och valmanifest bygger på projektet "Vi vill....! Hundra år av partipolitiska viljeyttringar" som genomfördes vid Svensk samhällsvetenskaplig datatjänst (SSD) 2000-2002. Projektet syftade till att sammanställa de partiprogram och manifest som de politiska partierna producerat under 1900-talet. I dessa texter kan man spåra partiernas utveckling, både vad gäller språkbruk, politik och ideologi. De ger även en god överblick över de frågor som varit väsentliga för vårt lands utveckling.

Samtliga partiprogram och valmanifest i databasen finns i .pdf och .txt format. De finns även tillgängliga hos Språkbanken som en korpus vilket medför ytterligare möjligheter för forskning på materialet.

Urvalet av valmanifest omfattade till en början endast riksdagspartier, då det baserades på Sven-Olov Håkansson studie "Svenska valprogram 1902-1952" samt forskningsprojektet "Partiernas opinionspåverkan", POP, av Peter Esaiasson och Nicklas Håkansson. Materialet har sedan kompletterats och urvalet har breddats till att exempelvis omfatta dokument för Europaparlamentet samt för partier utanför riksdagen. Fortfarande saknas ett okänt antal dokument som skulle kunna ingå i samlingen.

Datasetet består av:
- zip-filen "Svenska partiprogram och valmanifest" innehåller alla partidokument i .pdf och .txt format.
- Dokumentationsfilerna "Partidokument", i .xlsx och .csv -format, listar alla dokument, deras typer, källor och rubriker
- readme-fil

Partidokumenten finns också tillgängliga och sökbara via https://snd.gu.se/sv/vivill
Svenska partiprogram och valmanifest
Keywords: internal politics; inrikespolitik; party politics; partipolitik; political change; politisk förändring; political parties; politiska partier; election campaigns; valkampanjer; electoral issues; valfrågor; political manifestos; politiska manifest; political parties; partier; political change; politisk förändring; election campaigns; valkampanjer; political ideologies; politiska ideologier; party program; partiprogram; election manifesto; valmanifest; Elections; Val; Political ideology; Politisk ideologi; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap